Occipitocervical Dislocation in Low-Energy Trauma - Celeste Tavolaro; Richard Bransford; Aditya Yerrapragada; Carlo Bellabarba; Haitao Zhou (Case Reports in Orthopedics)
Traumatic occipitocervical dislocation (OCD) is described in the literature as a potentially fatal injury secondary to high-energy trauma. We describe a case of OCD occurring in a patient who sustained a ground-level fall whose only clinical symptom was posterior neck pain without neurologic compromise. Computed tomography (CT) and magnetic resonance imaging (MRI) were used to diagnose severe injury to the structurally important ligamentous complex that stabilizes the base of the skull to the spine, along with unstable fractures of the occipital condyle and C1. Emergent surgical instrumentation and fusion of occiput-C2 was performed. Postoperatively, neurologic integrity was maintained. This case illustrates that traumatic OCD is not exclusively secondary to high-energy mechanisms. It also demonstrates that severe neck pain as the only clinical manifestation in a patient with head or neck low-energy trauma is suggestive of a possible OCD. We highlight the importance of the use of head and neck CT as the first imaging-based diagnostic tool to aid in identifying this injury. Finally, surgical stabilization should be performed as soon as possible to minimize neurologic sequelae.